Influence of organic and inorganic fertilizers on soil fertility and productivity of wheat (Triticum aestivum) - KUMAR, DEEPENDRA; SINGH, SANDEEP; SINGH, JAGPAL; SINGH, S P (The Indian Journal of Agricultural Sciences, 2015)
A field experiment was conducted at Bichpuri (Agra) during rabi season of 2006-07 and 2007-08 to assess the effect of organic and inorganic fertilizers on wheat (Triticum aestivum L.) productivity and soil fertility. The grain and straw yields of wheat increased significantly with increasing levels of NPK fertilizers up to 150% NPK. The average increase in grain and straw yield over the control was 29.7 and 32.3 and 46.2 and 56.4 % with the application of 100 and 150% NPK, respectively. There was a significant increase in uptake of nutrients by wheat crop up to 150% NPK and in Zn uptake up to 100% NPK. Integrated use of fertilizers with S and Zn increased the grain and straw yield by 32.0 and 43.4 and 35.5 and 45.5 % over control, respectively. The highest grain and straw yield was recorded with 100% NPK + 12.5 tonnes FYM/ha with a record of 46.5 and 57.7 % increase over control (28.73 and 39.87q/ha ) while the application of 100% NPK + 7.5 tonnes GLM/ha ( 42.7 and 45.9 %) was on par with 150% NPK. The combined use of 100% NPK + 12.5 tonnes FYM/ha gave the highest net return and benefit:cost ratio. In general, fertilizer treatments including FYM proved superior to no FYM in respect of yield of protein. The maximum uptake of NPK by the crop was noted with 150% NPK which was statistically at par with 100% NPK + 12.5 tonnes FYM/ha and those of S and Zn with 100% NPK + 20 kg S/ha and 100% NPK + 5 kg Zn/ha, respectively. Integrated use of FYM with mineral fertilizers improved the organic carbon status and available N, P, K, S and Zn in soil thereby, sustaining the soil health. The omission of S and Zn in fertilizer schedule caused a depletion in the available S and Zn status of soil.